Ecocentrism Values in the Pasang Tradition of the Kajang Ethnic Group: A Study of Literary Ecology - Talib, Jihad; Supriadi, Supriadi; Hidayanti, Rahma; Mamah, Manavavee (Faculty of Humanities, Universitas Jenderal Soedirman, 2024)
This article discusses the ecocentrism values in the Pasang tradition of the Kajang ethnic community (Pasang ri Kajang) in South Sulawesi. Garrard Greg's ecocritical approach reveals the relationship between humans and the environment in the Pasang ri Kajang tradition. Data were collected through interviews, literature studies, and text analysis and then analyzed qualitatively. The results of the study indicate that the Kajang ethnic community based on Pasang ri Kajang guides their lives through the principles of kamase-masea (simple living), lambusu (honesty), gettang (firmness), and sabbara na appisona (patient and sincere) in everyday life. Pasang ri Kajang regulates the management and utilization of forests in settlements. Forests by the Kajang ethnic group are divided into three areas: borong karamaka (sacred forest), borong batasayya (border forest), and borong luara' (people's forest). The ecocentric values in Pasang ri Kajang that were found were 1) nature as the center of human life, 2) interdependence of humans with nature, and 3) harmony between humans and nature. These three ecocentrism values emphasize that Pasang ri Kajang can be a source of environmental conservation models based on local wisdom.